Anesthesia for Cesarean Section: Retrospective Comparative Study - Al-Husban N; Elmuhtaseb MS; Al-Husban H; Nabhan M; Abuhalaweh H; Alkhatib YM; Yousef M; Aloran B; Elyyan Y; Alghazo A (Dove Medical Press, 2021)
Naser Al-Husban,1 Mohammad Sami Elmuhtaseb,1 Hedaieh Al-Husban,2 Mohammed Nabhan,3 Hamza Abuhalaweh,3 Yasmine Mohamed Alkhatib,3 Maysa Yousef,3 Bayan Aloran,3 Yousef Elyyan,3 Asma Alghazo3 1Faculty of Medicine, The University of Jordan, Amman, Jordan; 2Al-Noor Fertility Center, Eye Specialty Hospital, Amman, Jordan; 3Obstetrics and Gynecology Department, Jordan University Hospital, Amman, JordanCorrespondence: Naser Al-HusbanFaculty of Medicine, The University of Jordan, P O Box 2194, Amman, 11941, JordanTel +962-772086080Fax +96264643217Email Husban48@yahoo.comBackground: Cesarean section is a widely performed surgery.Objective: To compare anesthetic types regarding feto-maternal outcomes.Materials and Methods: Retrospective comparative study of 3599 cesarean sections (emergency and elective categories).Results: Mean APGAR score was statistically higher in the spinal than general anesthesia among the emergency category, P = 0.000 and 0.026, respectively, with no significant difference in the elective category. Estimated blood loss among the elective category was statistically significantly higher in the spinal than general anesthesia, P = 0.001. However, among the emergency category, it was significantly higher in the general than in spinal or epidural anesthesia, P = 0.000. Diclofenac sodium was used more after spinal than general anesthesia (P = 0.000), with no significant difference between epidural and general or between epidural and spinal anesthesia. Pethidine hydrochloride (HCL) was used more after general than after spinal anesthesia (P = 0.000). However, pethidine HCL use was not statistically significantly different between spinal and epidural anesthesia. In the elective category, paracetamol was requested more after spinal than epidural or general anesthesia, P = 0.000. No significant difference was seen between epidural and general anesthesia, P = 1.000. No statistically significant difference was found among the anesthetic types in both categories regarding tramadol HCL. Length of hospital stay, operative time and neonatal intensive care unit admission were not statistically different between anesthetic modes. In the emergency category, significantly higher percentage of patients were satisfied with and would recommend epidural anesthesia.Conclusion: There was no statistically significant difference among the three types of anesthesia regarding neonatal intensive care admission and length of hospital stay for emergency and elective categories. APGAR score was higher with spinal than with general anesthesia in the emergency category with no significant difference in the elective category. More diclofenac sodium and paracetamol and less opioids were used after regional than after general anesthesia. Satisfaction was higher with epidural anesthesia.Limitations: Retrospective and single centered.Keywords: cesarean section, spinal, epidural, general, anesthesia, feto-maternal, outcome